Вы находитесь на странице: 1из 5

derivatives
formulas

1
Definition of the derivative
The definition of the derivative, also called the diﬀerence quotient, is the slope of the
tangent line, which is given by

## f (a + h) − f (a) f (x) − f (a)

f ′(a) = lim or f ′(a) = lim
h→a h x→a x−a

Diﬀerentiability
• A function is diﬀerentiable at a if f ′(a) exists

## • A function is diﬀerentiable on an open interval (a, b) if it is diﬀerentiable at every

number in the interval

## • If f is diﬀerentiable at a, then f is continuous at a

Derivative rules
d
(x ) = n x
n n−1
Power rule
dx

d
Product rule [ f (x)g(x)] = f ′(x)g(x) + f (x)g′(x)
dx

d x [ g(x) ]
d f (x) f ′(x)g(x) − f (x)g′(x)
Quotient rule =
[g(x)]
2

d
Chain rule [ f (g(x))] = f ′(g(x))g′(x)
dx

## Derivative of exponential functions

d d
(e ) = e ln e = e (1) = e (a ) = a ln a
x x x x x x
dx dx

2
Derivatives of logarithmic functions
d a d a
(a logb )
x = ( a ln x ) =
dx x ln b dx x

## Derivatives of trig functions

d d
dx [
a sin ( f (x))] = a cos ( f (x)) ⋅ f ′(x)
dx [
a csc ( f (x))] = − a csc ( f (x)) cot ( f (x)) ⋅ f ′(x)

d d
dx [
a cos ( f (x))] = − a sin ( f (x)) ⋅ f ′(x)
dx [
a sec ( f (x))] = a sec ( f (x)) tan ( f (x)) ⋅ f ′(x)

d d
dx [ a tan ( f (x))] = a sec2 ( f (x)) ⋅ f ′(x)
dx [ a cot ( f (x))] = − a csc2 ( f (x)) ⋅ f ′(x)

## Derivatives of inverse trig functions

d a ⋅ f ′(x) d a ⋅ f ′(x)
dx [ a sin−1 ( f (x))] =
dx [ a csc−1 ( f (x))] = −
1 − [ f (x)] f (x) [ f (x)] − 1
2 2

d a ⋅ f ′(x) d a ⋅ f ′(x)
dx [ a cos−1 ( f (x))] = −
dx [ a sec−1 ( f (x))] =
1 − [ f (x)] f (x) [ f (x)] − 1
2 2

d a ⋅ f ′(x) d a ⋅ f ′(x)
dx [
)]
dx [
( ( )]
−1 −1
a tan f (x) = a cot f (x) = −
1 + [ f (x)] 1 + [ f (x)]
2 2

## Derivatives of hyperbolic trig functions

d d
dx [ a sinh ( f (x))] = a cosh ( f (x)) ⋅ f ′(x)
dx [ acsch(f(x))] = − acsch(f(x))coth(f(x)) ⋅ f′(x)

d d
dx [ a cosh ( f (x))] = a sinh ( f (x)) ⋅ f ′(x)
dx [ asech(f(x))] = − atanh(f(x))sech(f(x)) ⋅ f′(x)

3
d d
dx [ a tanh ( f (x))] = asech2(f(x)) ⋅ f′(x)
dx [ a coth ( f (x))] = − acsch2(f(x)) ⋅ f′(x)

## Derivatives of inverse hyperbolic trig functions

d a ⋅ f ′(x) d a ⋅ f ′(x)
dx [ a sinh−1 ( f (x))] =
dx [ acsch−1(f(x))] = −
1 + [ f (x)] [ f (x)] + 1
2 2
| f (x) |

d a ⋅ f ′(x) d a ⋅ f ′(x)
dx [ a cosh−1 ( f (x))] = −
dx [ asech−1(f(x))] = −
[ f (x)] − 1 f (x) 1 − [ f (x)]
2 2

d a ⋅ f ′(x) d a ⋅ f ′(x)
dx [
( f (x))] =
dx [
( f (x))] =
−1 −1
a tanh a coth
1 − [ f (x)] 1 − [ f (x)]
2 2

## Definitions of hyperbolic trig functions

e x − e −x 1
sinh x = cschx =
2 sinh x

e x + e −x 1
cosh x = sechx =
2 cosh x

sinh x cosh x
tanh x = coth x =
cosh x sinh x

## Hyperbolic trig identities

sinh(−x) = − sinh x cosh(−x) = cosh x

## cosh2 x − sinh2 x = 1 1 − tanh2 x = sech2x

sinh(x + y) = sinh x cosh y + cosh x sinh y cosh(x + y) = cosh x cosh y + sinh x sinh y

## Нижнее меню

### Получите наши бесплатные приложения

Авторское право © 2021 Scribd Inc.